LINGUOCOGNITIVE AND CULTURAL ANALYSIS OF THE CONCEPT "FATHER" IN UZBEK AND ENGLISH LANGUAGES - Ismoilova Iroda Abduvasitovana (International Journal of Literature and Language Studies, 2026)
This article presents a comprehensive linguocognitive and cultural analysis of the concept "father" (English: Father; Uzbek: Ota) within the frameworks of modern cognitive linguistics and linguoculturology. By synthesizing research from 29 distinct sources, including monographs, dissertations, and corpus-based studies, the research explores how paternal roles are verbalized through proverbs, idioms, and literary texts. The findings indicate a significant cultural divergence: the English concept emphasizes individual mentorship and "caring masculinities," whereas the Uzbek concept is rooted in sacred authority, family unity, and ancestral lineage. This study employs the Natural Semantic Metalanguage (NSM) and Conceptual Metaphor Theory to unpack the semantic molecules and cultural codes inherent in each language.